OPTIMISATION OF AVIATION HUMAN RESOURCES: THE ROLE OF TRAINING, DISCIPLINE AND JOB SATISFACTION IN ENSURING FLIGHT SAFETY - Helga Tharadipa; Ferikawita M. Sembiring (SOSIOEDUKASI, 2026)
Commercial aviation has experienced significant growth in recent years; in 2024, passenger growth reached 54.76 million. This is inseparable from supporting factors such as aviation security, where Aviation Security personnel serve as a strategic element responsible for flight safety. However, the performance of Aviation Security personnel at Terminal 3 still faces obstacles. Field phenomena indicate low work discipline with an average lateness rate of 35.83% and a competency urgency where 96% of personnel require additional training. Additionally, a pre- research survey revealed a job satisfaction level of 76% and performance realization of 68%, both still below the management standard of 90%. The objective of this study is to analyze the factors influencing the performance of these Avsec personnel, specifically at Terminal 3 of Soekarno-Hatta Airport. The sample consists of 200 respondents determined using a saturated sampling technique, focusing on Aviation Security personnel assigned to Security Check Point 2. Data collection utilized an online questionnaire instrument. Data analysis was undertaken employing SEM-PLS 4. On the basis of the analytical outcomes, it may be adduced that, with respect to direct effects, training exerts a positive and statistically significant influence on performance, whereas work discipline does not manifest a positive effect on performance. Nonetheless, in regard to indirect effects, both training and work discipline evince a positive and significant influence on the performance of Aviation Security personnel when their effects are channelled through the mediating construct of job satisfaction. The research implications suggest that increased training activities, work discipline behavior, and job satisfaction impact performance, thereby enhancing the performance of Aviation Security personnel as the front line of aviation security operations.